Upaya Meningkatkan Sosialisasi Pada Klien Menarik Diri Di RSJD Arif Zainudin Surakarta - Ambarwati, Desi Wahyu, Arif Widodo, A. Kep, M.Kes (2016)
Background: According to the World Health Organization (WHO) in 2009, approximately 450 million people worldwide had a mental disorder. Mental disorders are circumstances that interfere in the process of living in the community due to their mental disorder that includes emotions, thoughts, behaviors, feelings, motivation, willingness, desire, power teller himself, and perception. One form of psychiatric disorders that have a high severity is schizophrenia. Schizophrenia is a severe mental disorder characterized by an inability to communicate or decline, impaired reality (hallucinations and delusions), unnatural or blunt affective, cognitive impairment and difficulty performing daily activities. Negative symptoms in schizophrenia causes the client impaired social function, namely social isolation. Social isolation is a disorder that causes the behavior maladptif interpersonal and social functioning disrupt a person as a result of an inflexible personality. Social isolation is one of the negative symptoms in schizophrenia are used by clients to shy away from other people so that unpleasant experiences in dealing with other people does not happen again. Objective: In order to determine the increase socialization in patients with social isolation: withdrawal after therapeutic communication in nursing. Methods: The author uses descriptive method with case studies for 3x24 hours in RSJD Arif Zainudin Surakarta. Result: The client is able to determine the patient's efforts to increase socialization in social isolation: withdrawal after therapeutic communication in nursing. Conclusion: The cooperation between client, family, and health personnel is critical to the success of a nursing care.